Subaltern childhood: historical dimensions of inequalities in the conditions of being a child (Brazil, first republican decades) - Cynthia Greive Veiga (Universidade Federal de Santa Catarina, 2019)
The article deals with the perspective of the production of subaltern childhood, through the theoretical reference of sociologist Norbert Elias and post - colonialist authors,  specialists in "subaltern studies" such as Gayatri Spivak, Andre Quijano and Enrique Dussel. For the development of the theme, a historical research is carried out, using diverse documentary sources, on the  differentiation and school inequality, with emphasis in the first republican decades and in the state of Minas Gerais. It is discussed how the differentiated and unequal school, associated to child labor, deepened the inequalities of the condition of being a child, contributing to the subaltern production of poor, black and mestizo children and to the stigma of their inferiority.